The Relation Between Knowledge and Attitude towards Behavior of Personal Protective Equipment Usage in Nurses - Gading Diah Zahara Putri; Y. Denny A. Wahyudiono (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Nurses are health workers who have the highest intensity of interactions with patients, so they have high risk of exposure to hazards in a workplace. Work accidents and nosocomial infections are hazards in hospitals that can threaten the safety and health of nurses. The proper use of Personal Protective Equipment is, therefore, mandatory to be implemented as an effort to prevent and minimize the risk of exposure or infection. This research was conducted to identify nurses’ behavior of Personal Protective Equipment (PPE) usage as well as to identify the relation between the level of knowledge and attitude as an internal factor of an individual in nurses’ behavior of PPE usage. Method: The research method used was observational with a cross-sectional study research design. The sample used in this research was determined by the total number of population, which was 12 nurses of pulmonary inpatient rooms at RSU Haji Surabaya in January-February 2020. The process of collecting data was done through interviews, questionnaires and observation on nursing care. The variables in this research were the level of knowledge, attitude, and behavior of PPE usage. Results: Most of the nurses had poor behavior (50%) of PPE usage with the majority having a moderate level of knowledge and attitude. Conclusion: There was a positive relation with strong correlation (ρ=0.635) between the level of knowledge and quiet strong correlation (ρ=0.417) between attitude that nurses had with their behavior of PPE usage.Keywords: attitude, behavior of personal protective equipment usage, knowledge, nurses